Names of some of the Persons who have Original Copies of the National Solemn League and Covenants - Laing, David (Proceedings of the Society of Antiquaries of Scotland, 1862)
A re-publication of David Laing’s paper on who owns copies of some Protestant documents from the sixteenth century. This paper was originally delivered in May 1847. He also offers descriptions of the contents and significance of these documents, and notes that there are occasionally some differences between copies, usually in who signed the document.